Downregulation of Microvascular Endothelial Type B Endothelin Receptor is a Central Vascular Mechanism in Hypertensive Pregnancy - Mazzuca, Marc Q. (2014)
Preeclampsia is a pregnancy-related disorder characterized by hypertension (HTN) with unclear mechanism. Studies have shown endothelial dysfunction and increased endothelin-1 (ET-1) levels in hypertensive-pregnancy (HTN-Preg). ET-1 activates endothelin receptor type-A (ET(A)R) in vascular smooth muscle to induce vasoconstriction, but the role of vasodilator endothelial ET(B)R in the changes in blood pressure (BP) and vascular function in HTN-Preg is unclear. To test if downregulation of endothelial ET(B)R expression/activity plays a role in HTN-Preg, BP was measured in Norm-Preg rats and rat model of HTN-Preg produced by reduction of uteroplacental perfusion pressure (RUPP), and mesenteric microvessels were isolated for measuring diameter, [Ca(2+)](i), and ET(A)R and ET(B)R levels. BP, ET-1 and KCI-induced vasoconstriction and [Ca(2+)](i) were greater in RUPP than Norm-Preg rats. Endothelium-removal or microvessel treatment with ET(B)R antagonist BQ-788 enhanced ET-1 vasoconstriction and [Ca(2+)](i) in Norm-Preg, but not RUPP, suggesting reduced vasodilator ET(B)R in HTN-Preg. ET-1+ET(A)R antagonist BQ-123, and ET(B)R agonists sarafotoxin 6c (S6c) and IRL-1620 caused less vasorelaxation and nitrate/nitrite production in RUPP than Norm-Preg. The NOS inhibitor L-NAME reduced S6c- and IRL-1620-induced relaxation in Norm-Preg but not RUPP, supporting that ET(B)R-mediated NO pathway is compromised in RUPP. RT-PCR, Western blots and immunohistochemistry revealed reduced endothelial ET(B)R expression in RUPP. Infusion of BQ-788 increased BP in Norm-Preg, and infusion of IRL-1620 reduced BP and ET-1 vasoconstriction and [Ca(2+)](i) and enhanced ET(B)R-mediated vasorelaxation in RUPP. Thus downregulation of microvascular vasodilator ET(B)R is a central mechanism in HTN-Preg, and increasing ET(B)R activity could be a target in managing preeclampsia.